Modeling and simulation of thermal behavior in field effect transistor systems - KHALFAOUI Achref Abdelhamid; SOUD Brahim; MAAMRI Khemais (University of Shahid Hama Lakhdar - El Oued, 2024)
The field effect transistor is the backbone of semiconductor electronics today. Among the transistor devices used is the metal semiconductor field effect transistor (MESFET). This device has an important role in electronic circuits in terms of resistance to the passing electric current and controlling the intensity of this current. As the size of the device decreases on the nanoscale, the heat generated affects the efficiency of the device. In this work, we studied the heat transfer inside the MESFET device based on gallium arsenide using the lattice Boltzmann method (LBM) with the effect of the specularity parameter which affects the thermal conductivity of the device and a change in the device substrate where used silicon, silicon oxide and gallium arsenide . The results showed that the device based on silicon substrate is less hot than the device based on silicon oxide and gallium arsenide, and that increasing the specularity coefficient has a positive effect on reducing the temperature of electronic devices ترانزستور ذو التأثير الحقلي هو العمود الفقري لإلكترونيات أشباه الموصلات اليوم، من بين اجهزة الترانزستور المستعملة هو حيث ان هذا الجهاز له دور مهم في الدوائر الالكترونية )MESFET( ترانزستورمعدني شبه موصل ذو التأثير الحقلي ميسفت من حيث المقاومة التيار الكهربائي المار والتحكم في شدة هذا التيار .ومع تناقص حجم الجهاز على مقياس النانو، فإن الحرارة المتولدة تؤثر على كفاءة الجهاز .في هذا العمل قمنا بدراسة الانتقال الحراري داخل جهاز ميسفت المعتمدة على زرنيخيد الغاليوم مع تأثير معامل الانعكاسية الذي يؤثر على التوصيل الحراري للجهاز وتغيير في ركيزة الجهاز حيث تم استعمال سليكون واوكسيد سليلكون و زرنيخيد الغاليوم، وذلك باستخدام طريقة شبكة بولتزمان .أظهرت النتائج أن الجهاز المعتمد على ركيزة السيليكون أقل حرارة من الجهاز المعتمد على واوكسيد سليلكون و زرنيخيد الغاليوم ، كما أن زيادة معامل الانعكاسية له تأثير إيجابي على خفض درجة حرارة الأجهزة الإلكترونية.
Master's thesis specializing in energy
Keywords: MESFET; heat transfer; Lattice Boltzmann method; Gallium arsenide; Substrate; ميسفت؛ انتتقال الحرارة ؛ طريقة شبكة بولتزمان ؛ زرنيخيد الغاليوم ؛ الركيزة